Evidence for the Expression of Urokinase-type Plasminogen Activator by Human Venous Endothelial Cells In Vivo - Camoin, L.; Pannell, R.; Anfosso, F.; Lefevre, J. P.; Sampol, J.; Gurewich, V.; Dignat-George, F. (Thrombosis and Haemostasis, 1998)
Endothelial cells (ECs) in culture synthesize and secrete urokinase-type plasminogen activator (u-PA), but the normal vascular endothelium is believed to synthesize only tissue plasminogen activator (t-PA), which is thought to be responsible for intravascular fibrinolysis. More recently, animal studies have shown that the biological role of u-PA in fibrinolysis has been underestimated, prompting a re-examination of its synthesis by the endothelium. In this study, we investigated whether u-PA was synthesized by non-atherosclerotic endothelial cells in vivo by testing ECs dislodged by venipuncture from 12 normal volunteers and 17 patients admitted for plasmapheresis. The ECs were isolated with an anti-endothelial monoclonal antibody coupled to immunomagnetic beads and characterized by morphology and by labelling for vWF, CD31, and UEA-1 binding. U-PA antigen was found in 50% of the ECs from the normal subjects and in 60% of those from patients. U-PA enzymatic activity on zymograms was detected in 50% of the normal samples and 60% of the patient samples, with the latter being more frequently and more strongly positive. U-PA mRNA was found in all the normal and patient samples tested. The results indicate that u-PA is synthesized by the venous endothelium in vivo but that its expression is highly variable.